Juridical Analysis QR Code Inclusion in Deed Seen From Act No. 2 of 2014 on the Amendment of Act No. 30 of 2004 about Notary - Angga Hardityo; Amin Purnawan; Setyawati Setyawati (Jurnal Akta, 2019)
A public official authorized to make an authentic deed regarding all actions, agreements and statutes that required by regulation or desired by the public interest that is expressed in an authentic deed is a Notary. The competent authorities have the duty and obligation to provide legal certainty on a whim deeds poured in the form of Deed. The times and the modern era such as the present need for security in the Deed to prevent counterfeiting deed, which one of them by using the QR Code in the Deed. Prudence needs to be done by a Notary Public, including keeping the deed of forgery measures. The safeguard measures need to take into account the provisions of legislation, as noted in UUJN Article 38 Paragraph (1) that: "each certificate shall consist of: a. Early Head Deed or Deed, b. Deed Agency, c. Closing the end Deed or Deed. This study aims to: 1) identify and analyze about the inclusion of the QR Code on the terms of the Deed Act No. 2 of 2014 on the change of Act No. 30 of 2004 concerning Notary; and 2) determine the position of Deed which included the QR Code on the deed by Act No. 2 of 2014 on the change of Act No. 30 of 2004 concerning Notary.Keywords: Analysis of Juridical; QR Code; Deed; Notary Law.